2018
DOI: 10.1016/j.ijheatmasstransfer.2018.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluid flow and heat transfer in a microchannel with interfacial electrokinetic effects

Abstract: The behaviour of microchannel flow of a nanofluid between two parallel flat plates in the presence of the electrical double layer (EDL) is investigated in this paper. The problem is formulated based on the Buongiorno nanofluid model with the electrical body force due to the EDL being considered in the momentum equation. As one of the highlights of the present investigation, the unphysical assumption introduced in previous studies often leading to the discontinuities of flow field that the electrostatic potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…is is consistent with the results obtained by Gong and Wu [56], according to which the resistance due to EDL is greater near the boundaries as compared to the mid part of the channel. Additionally, according to Zhao et al [54], the resistance in the velocity due to EDL is reduced with increase in κ, which is also evident in this case.…”
Section: Analysis and Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…is is consistent with the results obtained by Gong and Wu [56], according to which the resistance due to EDL is greater near the boundaries as compared to the mid part of the channel. Additionally, according to Zhao et al [54], the resistance in the velocity due to EDL is reduced with increase in κ, which is also evident in this case.…”
Section: Analysis and Discussionsupporting
confidence: 68%
“…With a uniform dielectric constant and the assumption that the thermal energy is significantly larger than the electrical potential, the Poisson-Boltzmann equation 1is reduced to [54] 1 r…”
Section: Mathematical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…2 , where T 0 represents the reference temperature and C 0 represents the volumetric fraction of the reference nanoparticle at the channel entrance. As the temperature T and volumetric fraction of the nanoparticle C vary linearly with x [21,22], we obtain With the above supposition, we see that the continuity equation is satisfied, and rest of the governing equations are simplified to the following equations:…”
Section: Mathematical Formulation For Other Fieldsmentioning
confidence: 92%
“…Particularly, Wang and Peng [21] found that the transmission and laminar heat transformation in microchannels is strange and quite complex with a conservatively sized condition. Zhao et al [22] discussed the heat transfer investigation of the nanofluid flow in a microchannel. Recently, some researchers studied the heat transfer flow of nanofluids for different purposes [23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%